The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.2042-7174.2012.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges: over-the-counter codeine supply from the codeine consumer’s perspective†

Abstract: The experiences of participants suggest a number of barriers exist to effective intervention for OTC codeine dependence in the community pharmacy setting. Identification of these barriers will provide an opportunity to more effectively target interventions to reduce harm related to OTC codeine products. Increased involvement of pharmacists in OTC codeine sales was associated with help-seeking by codeine users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 12 publications
11
61
0
Order By: Relevance
“…Similar to studies in Australia, France and the UK Nielsen et al, 2013;Roussin et al, 2013;Cooper, 2013b) and SACENDU data in 2014 , daily use of codeine containing medicines for more than six months was common, and progressed within weeks of commencing use. Side effects of use were typically opioid related (constipating, stomach cramps, nausea, (Pates et al, 2002;Nielsen et al, 2010), and appeared grounded in the context of self-regulation vulnerabilities (Khantzian.…”
Section: Strategies For Preventionsupporting
confidence: 75%
“…Similar to studies in Australia, France and the UK Nielsen et al, 2013;Roussin et al, 2013;Cooper, 2013b) and SACENDU data in 2014 , daily use of codeine containing medicines for more than six months was common, and progressed within weeks of commencing use. Side effects of use were typically opioid related (constipating, stomach cramps, nausea, (Pates et al, 2002;Nielsen et al, 2010), and appeared grounded in the context of self-regulation vulnerabilities (Khantzian.…”
Section: Strategies For Preventionsupporting
confidence: 75%
“…The study builds on findings reported in earlier qualitative studies with codeine dependents in the United Kingdom (Cooper, 2011(Cooper, , 2013a, Australia (Nielsen et al , 2013 and active online drug users (Van Hout, 2015). Given the covert nature of this issue, confounded by withdrawals, emotional distress and potential for serious co-morbidity, this study presents novel and meaningful illustration of the codeine misuse phenomenon, particularly within the Irish context.…”
Section: Discussionmentioning
confidence: 99%
“…Agyapong et al (2013) observe the potential for positive outcomes in deterrence of misuse of codeine following regulatory restrictions on visibility of products to the customer, restricted supply and pharmacist interventions at point of sale in Ireland. Of concern is that despite such proactive guidelines for restricted sales, relative ease of purchasing is reported by individuals misusing codeine containing products, with refusal at one pharmacy contributing to patterns of 'pharmacy hopping' (Nielsen, Cameron, & Pahokia, 2013;Van Hout, 2014b). These studies also describe customer tactics in securing a successful purchase as centring on appropriate appearance and pre rehearsed scripts in the event of pharmacist interrogation.…”
Section: Detection and Reduction Of Risk Of Codeine Misuse And Dependmentioning
confidence: 94%